Bystander interventions in out-of-hospital cardiac arrest according to geographical area type. (2nd May 2022) - Christensen, N; Folke, F; Juul Joergensen, A; Kollander Jakobsen, L; Samsoee Kjoelbye, J; Andelius, L; Tofte Gregers, M; Bundgaard Ringgren, K; Torp-Pedersen, C; Malta Hansen, C
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): TrygFonden Introduction: Bystander interventions and survival after out-of-hospital cardiac arrest (OHCA) have increased remarkably in Denmark over the last years. Even though 75% of all OHCA occur in residential areas, most interventions to increase bystander interventions have focused on public places. This study assessed bystander interventions (cardiopulmonary resuscitation [CPR] and defibrillation) according to area type. Methods: We included bystander witnessed OHCAs from the Danish Cardiac Arrest Registry (2016-2019) with a known geographical location. Urban Atlas is an international data base covering 40% of Denmark, which uses satellite images to divide areas into different area types. In this study, Urban Atlas was used to identify and geocode OHCAs within the following subgroups: high density residential areas (defined as average degree of soil sealing >50%), low density residential areas (average degree of soil sealing <50%), public and industrial sites, nature, sport and leisure facilities, transportation (e.g. airport and railway stations), and fast transit roads. Results: A total of 5, 180 bystander witnessed OHCA were covered by Urban Atlas and included. The proportion of bystander interventions was lowest in residential areas where most OHCAs occurred (Figure 1). The proportion of bystander interventions was highest in sport and leisure areas and transportation sites. The proportion of bystander defibrillation increased 5-fold in transportation sites and 3-fold in sports and leisure sites compared with residential areas. Conclusion: Patients with OHCA in transportation areas and sports and leisure areas were substantially more likely to receive bystander CPR and defibrillation, highlighting the success of initiatives to increase bystander interventions in public areas. Bystander defibrillation was lowest in residential areas supporting further efforts, such as smartphone activated volunteer responder activation, to improve bystander defibrillation in residential areas.